Adding Examples to the ASA–Physical Status Classification Improves Correct Assignment to Patients. Issue 5 (October 2017) - Hurwitz, E. E.; Simon, M.; Vinta, S. R.; Zehm, C. F.; Shabot, S. M.; Minhajuddin, A.; Abouleish, A. E.
Abstract : (Abstracted from Anesthesiology, 126(4):614–622, 2017) The main objective of this study was to examine whether including publicly available American Society of Anesthesiologists (ASA)–approved examples for the ASA Physical Status classification system improves correct assignment both by non–anesthesia-trained and anesthesia-trained clinicians.